RESEARCH OF THE COGNITIVE AREAS OF PERSONALITY OF THE MODERN SCHOOL TEACHER - Ismailova Dilbar Ruzmatovna (Journals Park Publishing, 2023)
This article is based on various teaching methods and innovations aimed at the development of the teacher's personality in the modern education system. Also, the modernization of the education system in Uzbekistan is defined as how to achieve a new quality of education.
Keywords: cognitive field, axiological approach, value, mental knowledge, cognitive competence, methodology, pedagogical practice, personal skill.